Using Social Media Promotions and Mixed Marketing Methods: Analysis Increasing the Interest of Transportation Jaklingko Passengers - Prima Widiyanto; Ika Utami Yulihapsari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this manuscript is to search the literature to support the variables of this manuscript and to provide results for consideration in future studies as a research gap or alongside other research items. This research used the primary literature survey that was the basis for writing this article. There were no respondents and no data processing was used. The framework results can be used as a novelty in this study. The results of this literature review present several key articles containing the investigated variables. The implication of this study is that there must be other variables that can support the significance of the dependent variable.